2016
DOI: 10.1111/tbed.12474
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial Infections in Rabbits: From the Wild to the Laboratory

Abstract: Tuberculous mycobacterial diseases such as leprosy and tuberculosis are ancient diseases that currently continue threatening human health in some countries. Non-tuberculous mycobacterial (NTM) infections cause a series of well-defined pathological entities, as well as some opportunistic diseases that have also increased worldwide, being more common among immunocompromised patients but rising also in immunocompetent individuals. Reports on natural infections by mycobacteria in rabbits are scarce and mainly invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…Badgers (Corner et al., , ; Lesellier et al., ), deer (Griffin et al., ; Palmer et al., ), wild boar (Garrido et al., ), rabbits (Arrazuria et al., ), ferrets (Qureshi et al., ; Cross et al., ) and possums (Ramsey et al., ; Tompkins et al., ). Little is known about the susceptibility of birds to M. bovis although they are generally thought to be resistant.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Badgers (Corner et al., , ; Lesellier et al., ), deer (Griffin et al., ; Palmer et al., ), wild boar (Garrido et al., ), rabbits (Arrazuria et al., ), ferrets (Qureshi et al., ; Cross et al., ) and possums (Ramsey et al., ; Tompkins et al., ). Little is known about the susceptibility of birds to M. bovis although they are generally thought to be resistant.…”
Section: Assessmentmentioning
confidence: 99%
“…Parameter 3 -Experimentally susceptible wildlife species (or family/orders) Badgers (Corner et al, 2007(Corner et al, , 2008Lesellier et al, 2009), deer Palmer et al, 2002), wild boar (Garrido et al, 2011), rabbits (Arrazuria et al, 2017), ferrets (Qureshi et al, 1999;Cross et al, 2000) and possums Tompkins et al, 2009). Little is known about the susceptibility of birds to M. bovis although they are generally thought to be resistant.…”
Section: Susceptible Animal Speciesmentioning
confidence: 99%
“…Although rabbits ( Oryctolagus cuniculus ) have been extensively and successfully used as models for the study of different types of TB, natural infection with mycobacteria seems to be very rare and almost limited to non‐tuberculous mycobacteria like M . avium subspecies (Arrazuria, Juste, & Elguezabal, ). Reports on naturally occurring MTBC infection in rabbits are restricted to one wild animal from New Zealand with generalized TB due to M .…”
Section: Introductionmentioning
confidence: 99%
“…bovis culture obtained from a skin lesion on the neck of a rabbit in Ireland (Delahay, De Leeuw, Barlow, Clifton‐Hadley, & Cheeseman, ). Several studies searched for MTBC in wild rabbits but failed to detect it (Arrazuria et al, ; Coleman & Cooke, ; Little, Swan, Thompson, & Wilesmith, ; Matos et al, ). As a result of lacking evidence of natural TB in rabbits, some authors suggested that rabbits could exhibit some resistance to M .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation